2019
DOI: 10.1007/s11892-019-1230-6
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Islet Transcriptional Enhancers and Diabetes

Abstract: Purpose of ReviewCommon genetic variants that associate with type 2 diabetes risk are markedly enriched in pancreatic islet transcriptional enhancers. This review discusses current advances in the annotation of islet enhancer variants and their target genes.Recent FindingsRecent methodological advances now allow genetic and functional mapping of diabetes causal variants at unprecedented resolution. Mapping of enhancer-promoter interactions in human islets has provided a unique appreciation of the complexity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Genome wide association studies (GWAS) to date have identified >240 loci that modulate risk for T2D (Mahajan et al 2018). However, these SNPs mostly occur in non protein-coding regions and are highly enriched to overlap islet-specific enhancer regions (Parker et al 2013;Pasquali et al 2014;Quang et al 2015;Thurner et al 2018;Cebola 2019). These findings suggest the variants likely affect gene expression rather than directly altering protein structure or function.…”
Section: Introductionmentioning
confidence: 99%
“…Genome wide association studies (GWAS) to date have identified >240 loci that modulate risk for T2D (Mahajan et al 2018). However, these SNPs mostly occur in non protein-coding regions and are highly enriched to overlap islet-specific enhancer regions (Parker et al 2013;Pasquali et al 2014;Quang et al 2015;Thurner et al 2018;Cebola 2019). These findings suggest the variants likely affect gene expression rather than directly altering protein structure or function.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, monogenic diabetes predominantly results from mutations in transcription factors, which are involved in pancreas development 4 . Moreover, genetic variants in or nearby some of these transcription factor genes have been associated with type 2 diabetes risk 5 .…”
Section: Introductionmentioning
confidence: 99%
“…However, gene expression represents the final outcome of a complex layer of genetic and epigenetic factors that determine islet cell fate [7][8][9] and identity [10,11]. Previous studies have explored pancreatic islet cellular identity by evaluating epigenomic features such as methylation [12][13][14], histone modifications [15][16][17][18], and enhancer regulatory regions [19][20][21][22][23][24]. While each of these factors contributes to defining and maintaining cell fate and identity, connecting chromatin accessibility differences to epigenetic factors promises to provide further insight into outstanding questions within the field.…”
Section: Introductionmentioning
confidence: 99%